Rat Hepatitis E Virus Linked to Severe Acute Hepatitis in an Immunocompetent Patient. (14th January 2019) - Andonov, Anton; Robbins, Mark; Borlang, Jamie; Cao, Jingxin; Hatchette, Todd; Stueck, Ashley; Deschambault, Yvon; Murnaghan, Kyle; Varga, Jessy; Johnston, Lynn
Abstract: Hepatitis E virus (HEV) is a major public health concern in developing countries where the primary transmission is via contaminated water. Zoonotic HEV cases have been increasingly described in Europe, Japan, and the United States, with pigs representing the main animal reservoir of infection. We report an unusual acute hepatitis infection in a previously healthy man caused by a rat HEV with a considerably divergent genomic sequence compared with other rat HEV strains. It is possible that rat HEV is an underrecognized cause of hepatitis infection, and further studies are necessary to elucidate its potential risk and mode of transmission. Abstract : Rat hepatitis E virus (HEV) with a considerably divergent genomic sequence compared with other rat HEV strains was identified as the cause of severe acute hepatitis in a previously healthy man with no known contacts with rodents or their droppings.